Les politiques de gestion insulaire dans l’archipel des Maldives - Caroline Rufin-Soler (Cybergeo, 2005)
The Maldives archipelago is a privileged field of observation for the analysis of a constraining development because of its insularity. Politics of insular development, are often controlled by the tourism development of the archipelago. We propose a multiscale analysis of the insular development, controlled by the tourism activity, which structure the archipelago.